The formation of the conception of the aesthete education by die means of theatrical art tn pedagogical theory in XIX-XX cen. (Pedagogy of Higher and Secondary Education, 2006)
In the article are depicted conceptual positions of pedagogues in the end of the XIX - the beginning of XX cen. that become the basically resources of aesthete development of individual child education.
Keywords: pedagogical ideas in XIX-XX cen.; aesthetic-art education; individual formation and theotrical art